Haunted ghost tour in New Mexico - Martin, Louise; Tafuni, Gabriele (Naperville, Illinois Hometown World, an imprint of Sourcebooks Kids, 2023)
"Experience a fa-BOO-lous Halloween with Little Ghost on a tour of all the landmarks you know and love in NEW YORK! Little Ghost is going on a spooky Halloween tour around New York, and you're invited to ride along! Take a trip with the Ghost family as they travel from New York City to Lake Placid and visit favorite landmarks such as the National Baseball Hall of Fame and the Statue of Liberty. Along the way, Little Ghost loves tricking everyone . . . until Little Ghost hears the biggest BOO ever! Make this Halloween season spook-tacular with this cute, not-so-scary rhyming picture book that takes you on an adventure through your home state.-- Amazon.com
113373
Keywords: Halloween -- Juvenile fiction; Autumn -- Juvenile fiction; Travel -- Juvenile fiction; New Mexico -- Juvenile fiction; Ghosts -- Fiction; Stories in rhyme; Ghost stories; Picture books; Fiction; Juvenile works